Human Thg1 displays tRNA-inducible GTPase activity. Issue 17 (15th September 2022) - Antika, Titi Rindi; Nazilah, Kun Rohmatan; Lee, Yi-Hsueh; Lo, Ya-Ting; Yeh, Chung-Shu; Yeh, Fu-Lung; Chang, Tien-Hsien; Wang, Tzu-Ling; Wang, Chien-Chia
Abstract: tRNA His guanylyltransferase (Thg1) catalyzes the 3′-5′ incorporation of guanosine into position -1 (G-1) of tRNA His . G-1 is unique to tRNA His and is crucial for recognition by histidyl-tRNA synthetase (HisRS). Yeast Thg1 requires ATP for G-1 addition to tRNA His opposite A73, whereas archaeal Thg1 requires either ATP or GTP for G-1 addition to tRNA His opposite C73. Paradoxically, human Thg1 (HsThg1) can add G-1 to tRNAs His with A73 (cytoplasmic) and C73 (mitochondrial). As N73 is immediately followed by a CCA end (positions 74–76), how HsThg1 prevents successive 3′-5′ incorporation of G-1/G-2/G-3 into mitochondrial tRNA His (tRNAm His ) through a template-dependent mechanism remains a puzzle. We showed herein that mature native human tRNAm His indeed contains only G-1. ATP was absolutely required for G-1 addition to tRNAm His by HsThg1. Although HsThg1 could incorporate more than one GTP into tRNAm His in vitro, a single-GTP incorporation prevailed when the relative GTP level was low. Surprisingly, HsThg1 possessed a tRNA-inducible GTPase activity, which could be inhibited by ATP. Similar activity was found in other high-eukaryotic dual-functional Thg1 enzymes, but not in yeast Thg1. This study suggests that HsThg1 may downregulate the level of GTP through its GTPase activity to prevent multiple-GTP incorporation into tRNAm His .